Caracterização dos empreendimentos e perfil dos empreendedores do centro comercial de Cerro Corá - RN - Borges, Lucas Querino da Costa (Universidade Federal Rural do Semi-Árido, 2016)
Currently much has been said about the entrepreneurial activity in Brazil and in the world, being a practice that grows at an accelerated rate, based on creativity and innovation, providing development with regard to economic and social framework. Considering the rate of new developments, this research seeks to visualize and characterize the current scenario Brazilian entrepreneur and specifically the city of Cerro Corá, located in the central middle region of Natal Rio Grande do Norte state. For the realization and development of this work, it was used as a methodology one bibliographic and documentary research by classical literature and field research, in addition to the case study. Thus, it applied a form where this is the question on gender, age and level of education of entrepreneurs, as well as the operating time, branch and size of the municipal enterprises. Showing their distribution according to the economic sectors and the use of information technology on the market. Later, identifying where results show that the municipality of Cerro Corá/RN portrays the predominance of male entrepreneurs and the high rate of small businesses.
Monografia
Keywords: Empreendedorismo; Perfil empreendedor; Cerro Corá - RN; Entrepreneurship; Entrepreneurial Profile; Cerro Corá/RN; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA